3a-2=2a-3

Simple and best practice solution for 3a-2=2a-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3a-2=2a-3 equation:


Simplifying
3a + -2 = 2a + -3

Reorder the terms:
-2 + 3a = 2a + -3

Reorder the terms:
-2 + 3a = -3 + 2a

Solving
-2 + 3a = -3 + 2a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-2a' to each side of the equation.
-2 + 3a + -2a = -3 + 2a + -2a

Combine like terms: 3a + -2a = 1a
-2 + 1a = -3 + 2a + -2a

Combine like terms: 2a + -2a = 0
-2 + 1a = -3 + 0
-2 + 1a = -3

Add '2' to each side of the equation.
-2 + 2 + 1a = -3 + 2

Combine like terms: -2 + 2 = 0
0 + 1a = -3 + 2
1a = -3 + 2

Combine like terms: -3 + 2 = -1
1a = -1

Divide each side by '1'.
a = -1

Simplifying
a = -1

See similar equations:

| 175-308= | | fx-gx=8 | | 5y=8y-20 | | -0.5(-2.94+3x)=-1.2x | | 39+19x=100 | | 2x^2*2x=3360 | | x(x+1)*(x+2)=3360 | | Y=9X^2+15X+52 | | 9X^2+15X+52=X | | d+2.8=9.5 | | ax+by+bx+ay= | | -2(3+m)=-3(1-m) | | 9x+4=7x+12 | | 2x+4y=200 | | 4-x^2=x^2-14 | | 8q-7=5q+11 | | 6(-2)=18 | | 4x-3-2x=9+2x-12 | | 0.5x-0.25=.92 | | 0.5x-0.25= | | 5/6(x-2)+1.3=7x/10+0.5x | | -10y=-60 | | 50s-13=55s-93 | | (2x-6)(x-4)(3x+3)=0 | | (2x-6)*(x-4)*(3x+3)=0 | | ((7-2)*3)*5= | | t^3-t-1=0 | | x-3(2x+3)=2(3-2x)-18 | | 12pq+6q= | | 2000=200t | | -6+c-4=-6 | | x-3(2x+3)=2(3-2x)-12 |

Equations solver categories